G160 Association Between External and Internal Dose of Diesel Soot (Black Carbon) in Healthy Schoolchildren: A Pilot Study. (4th June 2013) - Hussain, S; Grigg, J; Mushtaq, N; Dundas, I; Brugha, R
Abstract : Aims: Exposure to diesel soot (black carbon, BC) is linked to adverse health in children. A cross-sectional study reported that BC in airway macrophages (AM BC), a marker of inhaled dose of diesel soot, is associated with decreased lung function in healthy children [1]. These data are compatible with the reduction in growth of lung function associated with long-term exposure to elemental carbon reported in an 8 year epidemiological study of schoolchildren [2].To date, the determinants of AM BC are unknown. This is an important evidence gap since it is unclear whether policy-makers should target background BC, or peaks of freshly generated BC from roads. Using a newly developed portable monitor for BC, we sought to determine whether peaks in BC exposure are associated with airway macrophage black carbon (AM BC) in healthy schoolchildren. Methods: Sputum inductions were carried out at schools as previously described [1]. Following processing, mean AM BC (µm2) for 50 randomly selected AM was calculated using Image J software. Personal exposure to BC was measured by a portable aethalometer (MicroAeth AE51, Magee Scientific). This monitor continuously samples BC in the air and data is downloaded after 24 h using the microAethCOM PC-based software (Fig 1 ). The number of peaks of BC above 10000 ng/300 sec was determined for each child by inspection of the 24 h plot. Results: Twenty three children underwent sputum inductions. In the 15 children (65%) who produced sufficient AM for analysis, the median AM BC was 0.26278 µm2 (interquartile range (IQR) of 0.16164 to 0.42842 µm2). Personal 24 hour BC data was obtained in 13/15 children. The median BC exposure was 783758 ng (IQR: 336583.5 to 1321364.5 ng). Exposure peaks were caused by the school journey and cooking. No significant correlation was found between the number of peaks of carbon exposure above 10000 ng/300 sec and average AM BC (µm 2 ) (Fig 2 ). However the positive association (r = 0.40, Pearson coefficient) suggests that this pilot study may be underpowered. Conclusion: Linking external and inhaled dose of BC is feasible in schoolchildren, and may provide important insights into the determinants of inhaled dose of BC. References: Kulkarni N, Pierse N, Rushton L, Grigg J. "Carbon in airway macrophages and lung function in children." The New England Journal of Medicine 6, 355 (2006): 21–30. Gauderman, WJ, E Avol, F Gilliland, H Vora, D Thomas, K Berhane, R McConnell, N Kuenzli, F Lurmann, E Rappaport, H Margolis, D Bates and J Peters. "The effect of air pollution on lung development from 10 to 18 years of age." The New England Journal of Medicine 351, 11 (2004): 1057–1067.